"I might be shot at!" exploring the drivers to work in hostile environments using an intelligent careers perspective. Issue 4 (11th December 2017) - Dickmann, Michael; Watson, Ashley Helen
Abstract : Purpose: The purpose of this paper is to explore the factors which influence individuals to take up international assignments in hostile environments (HEs). Using an intelligent careers (IC) perspective, an expanded framework of expatriation drivers to work in hostile contexts is developed that comprises individual, organizational and location-specific factors. In addition, the understanding of career capital acquisition and transfer is refined. Design/methodology/approach: A "deviant" case study method to challenge the underlying assumptions of career capital maximization and transfer in global careers is used. To investigate the case, 25 individuals in an international development organization who had to decide whether to work in HEs were interviewed. Findings: Five insights into decision drivers and career capital effects associated with postings to HEs are presented. These span all three levels of individual, organizational and location-specific decision factors. Research limitations/implications: Due to the case study approach, the usual limitations of qualitative case-based research with respect to generalizability apply. In the conclusions three theoretical implications for the IC framework with respect to career capital acquisition, utilization and temporal effects are outlined. Practical implications: A range of practical implications in relation to the selection, talent management, performance and reward approaches as well as repatriation and family considerations in global mobility are explored. Social implications: The insights help organizations to design global mobility policies for HEs. In addition, individuals and their families benefit from greater clarity of global mobility drivers in the context of high risks. Originality/value: The drivers of individuals to accept assignments to HEs are under-researched. This paper operationalizes and applies a holistic decision to work abroad framework, expands the literature on of the motivations of individuals and develops valuable insights to nuance the IC framework.